ความชุกและปัจจัยที่เกี่ยวข้องกับโรคผื่นผิวหนังบริเวณมือของพยาบาลวิชาชีพโรงพยาบาลจุฬาลงกรณ์ - วีระ ปิยะสิงห์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
In Occupational Medicine practice, hand dermatitis is a common problem among health care personnel. However, there are few studies that assess epidemiology of this problem. Thus, the purpose of this cross-sectional descriptive study was to examine the prevalence and related factors of hand dermatitis among registered nurses at King Chulalongkorn Memorial Hospital. Study subjects were registered nurses who worked in nursing care in King Chulalongkorn Memorial Hospital. The data were collected from 1}340 registered nurses during October 2004 by using the self-administered questionnaires, with its response rate was 85.4 percent. The results showed that the prevalence of the hand dermatitis among registered nurses who work in nursing care in King Chulalongkorn Memorial Hospital during September 2003 to October 2004 occurred at the rate of 14.3 persons per 100 persons per year. The most prevalence of hand dermatitis were found among nurses with [is less than or equal to] 30 years age agroup, 1-10 years working experience and working in Internal Medicine unit. Factors which were statistically significant associated with hand dermatitis (p < 0.01) were: (1) personal factors such as history of previous atopic eczema (2) occupational exposure factors such as hibitane (chorhexidine) (3) domestic work factors such as plantation, but work environment factors were not significanty associated with hand dermatitis. This study suggests that hand dermatitis is common among registered nurses. Atopy, occupational exposure and domestic work are contributing risk factors of hand dermatitis.